Paul Bairoch. De Jéricho à Mexico : villes et économie dans l'histoire. Paris, Gallimard, 1985. (Col. Arcades) - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1986)
PAUL BAIROCH . De Jéricho á Mexico: villes et économie dans I´histoire, Gallimard, París, 1985.